Ultra-white high borosilicate glass and preparation method thereof
By pretreating quartz sand, the content of impurities and the surface activity is improved, the problem of reduced light transmittance of high borosilicate glass is solved, and the effect of ultra-white and high light transmittance is achieved, meeting the application needs in high-end fields.
Patent Information
- Application Number
- CN202411872639.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
AI Technical Summary
Due to the existence of impurity iron, high borosilicate glass has reduced light transmittance and poor optical performance, making it difficult to meet the demand for ultra-white high transmittance in high-end fields.
By pretreating quartz sand, including the use of acid leach and iron ion collector, the impurity iron content in the raw materials is effectively reduced, the surfactivity of quartz sand is improved, and a unified and tight network structure is formed, thereby improving the light transmittance of borosilicate glass.
It realizes the ultra-white and high light transmittance of high borosilicate glass, improves the mechanical properties and chemical stability of the glass, and meets the application needs in high-end fields.
Smart Images

Figure BDA0005196126390000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of borosilicate glass, and in particular relates to an ultra-white high-borosilicate glass and a preparation method thereof. Background Art
[0002] High borosilicate glass has high physical strength, good fire resistance, high mechanical and chemical stability, and compared with ordinary glass, high borosilicate has a very low thermal expansion coefficient due to its special combination and structure, and is not easy to burst or deform in high temperature environments. Therefore, it can be widely used in cinema projectors, chemical reactor inspection window covers, high-efficiency lamps and other devices that need to work under high temperature conditions or environments with drastic temperature changes. In addition, high borosilicate glass has high thermal stability, high softening point, and good thermal shock resistance, and can also be used in fields such as building fire protection.
[0003] However, as people's requirements for products are increasing, they must not only meet the requirements of fire prevention and lighting, but also have the characteristics of ultra-white high transmittance, light adjustment, thermal insulation, artistic decoration, photoelectric and photothermal conversion. However, the raw materials of high borosilicate glass will inevitably contain impurities such as iron, cobalt, nickel, and chromium. In particular, the impurity iron will have a greater impact on borosilicate glass, making the originally colorless and transparent glass appear yellow, yellow-green or blue-green, affecting the transmittance of the glass, resulting in the deterioration of the optical properties of the obtained borosilicate glass. Therefore, it is urgent to develop a borosilicate ultra-white glass with high glass transmittance that can be applied to high-end fields. Summary of the invention
[0004] The object of the present invention is to provide an ultra-white high-borosilicate glass and a preparation method thereof, so as to solve the problem that the high-borosilicate glass has a reduced light transmittance and a slight coloration due to the presence of impurity iron.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides an ultra-white high borosilicate glass, comprising the following raw materials in parts by weight:
[0007] 70-80 parts of pre-treated quartz sand;
[0008] B2O3 10-15 parts;
[0009] Al2O3 3-5 parts;
[0010] 1-2 parts of clarification aid;
[0011] Na2O 4-6 parts;
[0012] The pretreated quartz sand is obtained by acid leaching and pretreatment with an iron ion collector; the iron ion collector is tannic acid / polyacrylamide hydrogel.
[0013] Preferably, the clarification aid is sodium chloride.
[0014] Preferably, pre-treating quartz sand includes the following specific process steps:
[0015] S101. Add quartz sand to a strong acid aqueous solution and immerse for 5 to 10 days;
[0016] S102. Adjust the pH value of the solution to 3 to 4, add an iron ion collector and a dispersant, and stir and mix for 30 to 40 minutes;
[0017] S103. Pre-treated quartz sand is obtained by centrifugal separation, filtering, washing and drying.
[0018] Preferably, the amount of the iron ion collector added is 0.2-0.4% of the mass of the quartz sand.
[0019] Preferably, the dispersant includes a combination of one or more of sodium dodecylbenzene sulfonate, sodium lignin sulfonate, sodium lauryl ether sulfate and polyvinyl pyrrolidone; and the added amount of the dispersant is 0.05-0.1% of the mass of the quartz sand.
[0020] Preferably, the particle size of the quartz sand is 0.5 to 5 mm.
[0021] Preferably, the strong acid aqueous solution includes a combination of one or more of a hydrochloric acid aqueous solution, a nitric acid aqueous solution, a hydrofluoric acid aqueous solution and a sulfuric acid aqueous solution with a mass fraction of 20 to 30%.
[0022] By adopting the above technical scheme, the present invention adopts the form of pretreatment, which greatly reduces the impurity content in the raw material directly in the pretreatment link. Specifically, the conventional scheme is to add oxides during the preparation of borosilicate glass to reduce the influence of impure iron on the glass and improve the light transmittance of the glass. However, this method will introduce other cations into the glass, which will affect the coordination and connection relationship between the ions in the formation process of borosilicate glass, thereby affecting the mechanical properties and chemical stability of the obtained borosilicate glass. In order to further solve this problem, the present invention pretreats the raw material quartz sand.
[0023] First, through acid leaching, the iron ions in the quartz sand can be effectively leached into the leachate, and the silicon dioxide can be effectively retained due to its stable chemical properties and not easily dissolved by acid. The iron ions can be dissolved by acid due to their active chemical properties, thereby effectively separating the impurity iron from the quartz sand. In addition, the quartz sand treated with acid leaching improves the surface activity of the raw materials, which helps to form a unified network structure with boric acid and alumina during the preparation of high borosilicate glass, making the glass structure more compact and improving the strength of the obtained high borosilicate glass.
[0024] The leached iron ions are mostly in the form of a mixture of divalent iron ions and trivalent iron ions, among which trivalent iron ions are easily hydrolyzed to form iron hydroxide precipitation, which often exists in the form of amorphous colloids and is difficult to filter. Therefore, during the separation process, some iron ions will still remain on the surface of the quartz sand, which will affect the transmittance of the obtained high borosilicate glass. Therefore, after acid leaching, adding an iron ion collector to the leachate can effectively adsorb and compete for the iron ions in the solution, effectively avoiding the adsorption of iron ions on the surface of the quartz sand, and the iron ion collector is also easy to separate from the quartz sand, realizing the effective separation of impurity iron, thereby improving the transmittance of the high borosilicate glass.
[0025] Preferably, the raw materials of the tannic acid / polyacrylamide hydrogel include acrylamide and tannic acid in a mass ratio of 100:(4-6).
[0026] Preferably, the tannic acid / polyacrylamide hydrogel is coordinated with manganese ions.
[0027] Preferably, the tannic acid / polyacrylamide hydrogel is prepared according to the following method:
[0028] Preparation of hydrogel: Add tannic acid to water, stir to dissolve, then add acrylamide, initiator and cross-linking agent, stir and mix until completely dissolved, raise the temperature to 60-70°C, keep warm for 1-2 hours, wash and filter to obtain tannic acid / polyacrylamide hydrogel;
[0029] Coordinated manganese ions: Disperse tannic acid / polyacrylamide hydrogel in water, adjust the pH value to 6-6.5, increase the temperature to 30-35°C, add water-soluble manganese salt, stir the reaction for 30-60 minutes, and then keep warm at 4-6°C in a nitrogen atmosphere for 6-8 hours. Finally, wash, evaporate and freeze-dry to obtain tannic acid / polyacrylamide hydrogel coordinated with manganese ions.
[0030] Preferably, the amount of water-soluble manganese salt added is 1-3% of the mass of the tannic acid / polyacrylamide hydrogel.
[0031] Preferably, the water-soluble manganese salt includes a combination of one or more of manganese sulfate, manganese chloride, manganese nitrate, manganese acetate, manganese phosphate, manganese carbonate and manganese oxalate.
[0032] Preferably, the initiator includes a combination of one or more of ammonium persulfate, potassium persulfate, azobisisobutyronitrile and benzoyl peroxide.
[0033] Preferably, the cross-linking agent is N,N'-methylenebisacrylamide.
[0034] By adopting the above technical scheme, the iron ion collector adopted by the present invention is tannic acid / polyacrylamide hydrogel, wherein the phenol group and other functional groups contained in the tannic acid can form a stable complex with the iron ions as a ligand, and the hydrogel based on polyacrylamide has a highly branched structure and a cross-linked network structure, the active groups contained therein can attract iron ions, and the cross-linked structure also greatly increases the active sites contained in the hydrogel, which can well play the role of capturing and fixing iron ions, thereby realizing the effective removal of iron ions.
[0035] However, at the same time, since part of the iron ions leached out by acid still exist in the form of divalent iron ions, their coordination ability is slightly poor, and they will form microcrystals in the leachate, which is not conducive to the complete removal of iron ions. Therefore, manganese ions are pre-coordinated on the tannic acid / polyacrylamide hydrogel. The manganese-polyphenol coordination compound formed by the combination of manganese ions and polyphenols in tannic acid has a certain oxidation ability, which can first oxidize the divalent iron ions in the leachate into trivalent iron ions, thereby improving the coordination ability between iron ions and tannic acid / polyacrylamide hydrogel, and improving the removal rate of iron ions, thereby obtaining ultra-white high borosilicate glass.
[0036] In a second aspect, the present invention provides a method for preparing ultra-white high borosilicate glass, comprising the following process steps:
[0037] S201. Weigh the corresponding mass fractions of raw materials and mix them to obtain a premix;
[0038] S202. The premix is melted at a high temperature of 1650 to 1750° C. to obtain a borosilicate glass liquid;
[0039] S203. After being fully stirred and clarified, the borosilicate glass liquid is gradually cooled to remove bubbles and impurities, and finally formed and annealed to obtain ultra-white high-borosilicate glass.
[0040] Preferably, the gradient cooling is divided into a high temperature zone and a low temperature zone, and the borosilicate glass liquid is cooled in turn through the high temperature zone and the low temperature zone, wherein the temperature of the high temperature zone is 1450-1500°C; the temperature of the low temperature zone is 1300-1350°C.
[0041] Preferably, the molding temperature is 650-1100°C.
[0042] Preferably, the annealing temperature is 300-550°C.
[0043] Beneficial effects of the present invention:
[0044] 1. The present invention adopts the form of pretreatment to pretreat the raw material quartz sand, separates the iron ions in the quartz sand by acid leaching, and improves the surface activity of the quartz sand raw material, which is helpful to form a unified and tight network structure, thereby improving the strength of the borosilicate glass; after acid leaching, an iron ion collector is added to the leachate, which can effectively adsorb and compete for the iron ions in the solution, realize the effective separation of impurity iron, thereby improving the transmittance of the high borosilicate glass.
[0045] 2. The iron ion collector used in the present invention is tannic acid / polyacrylamide hydrogel, which can form a stable complex with iron ions. The cross-linked and branched network of the hydrogel can better attract and fix iron ions; and manganese ions are also pre-coordinated. The manganese-polyphenol coordination compound formed by the combination of manganese ions and polyphenols in tannic acid has a certain oxidation ability and can oxidize divalent iron ions into trivalent iron ions, making the iron ions easier to be adsorbed and removed, thereby obtaining ultra-white high borosilicate glass. DETAILED DESCRIPTION
[0046] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] Preparation Example
[0048] Preparation Example 1: An iron ion collector is prepared according to the following method:
[0049] Add 5 g of tannic acid to 600 mL of water, stir to dissolve, then add 100 g of acrylamide, 2 g of ammonium persulfate and 2 g of N,N'-methylenebisacrylamide, stir to mix until completely dissolved, raise the temperature to 60°C, keep warm for 1.5 h, wash and filter to obtain tannic acid / polyacrylamide hydrogel, i.e., iron ion collector.
[0050] Preparation Example 2, an iron ion collector, is different from Preparation Example 1 only in that the amount of tannic acid added is 4 g.
[0051] Preparation Example 3, an iron ion collector, is different from Preparation Example 1 only in that the amount of tannic acid added is 6 g.
[0052] Preparation Example 4, an iron ion collector, is different from Preparation Example 1 only in that the amount of tannic acid added is 2 g.
[0053] Preparation Example 5, an iron ion collector, is different from Preparation Example 1 only in that the amount of tannic acid added is 8 g.
[0054] Preparation Example 6, an iron ion collector, is different from Preparation Example 1 only in that tannic acid is not added.
[0055] Preparation Example 7, an iron ion collector, prepared according to the following method:
[0056] Add 5 g of tannic acid to 600 mL of water, stir to dissolve, then add 100 g of acrylamide, 2 g of ammonium persulfate and 2 g of N,N'-methylenebisacrylamide, stir to mix until completely dissolved, raise the temperature to 60°C, keep warm for 1.5 h, wash and filter to obtain tannic acid / polyacrylamide hydrogel, i.e., iron ion collector.
[0057] Take 100g of tannic acid / polyacrylamide hydrogel and disperse it in 500mL of water, adjust the pH value to 6, increase the temperature to 35°C, add 2g of manganese sulfate, stir the reaction for 60min, and then keep it warm at 4°C in a nitrogen atmosphere for 7h. Finally, wash, evaporate and freeze-dry to obtain tannic acid / polyacrylamide hydrogel coordinated with manganese ions, i.e., an iron ion collector.
[0058] Preparation Example 8, an iron ion collector, is different from Preparation Example 7 only in that the amount of manganese sulfate added is 5 g.
[0059] Example
[0060] Example 1, an ultra-white high borosilicate glass, is prepared according to the following method:
[0061] Pretreatment of quartz sand:
[0062] S101. Add 1 kg of quartz sand (average particle size 2 mm) to a 30% hydrochloric acid aqueous solution and immerse for 7 days;
[0063] S102. The pH value of the solution was adjusted to 3.5, 3 g of the iron ion collector prepared in Preparation Example 1 and 0.8 g of sodium dodecylbenzene sulfonate were added, and the mixture was stirred for 30 min;
[0064] S103. Pre-treated quartz sand is obtained by centrifugal separation, filtering, washing and drying.
[0065] Preparation of ultra-white high borosilicate glass:
[0066] S201 weighed 7.5kg of the pretreated quartz sand obtained above, 1.2kgB2O3, 0.4kgAl2O3, 0.15kg sodium chloride and 0.5kgNa2O were mixed to obtain a premix;
[0067] S202. The premix is melted at a high temperature of 1700° C. to obtain borosilicate glass liquid;
[0068] S203. After being fully stirred and clarified, the borosilicate glass liquid is gradually cooled. Specifically, the borosilicate glass liquid is cooled in a high temperature zone and a low temperature zone in turn, wherein the temperature of the high temperature zone is 1450°C; the temperature of the low temperature zone is 1300°C, bubbles and impurities are discharged, and finally, ultra-white high borosilicate glass is obtained through molding and annealing.
[0069] Example 2, an ultra-white high-borosilicate glass, is different from Example 1 only in that 4 g of the iron ion collector prepared in Preparation Example 2 is added in step S102.
[0070] Example 3, an ultra-white high-borosilicate glass, is different from Example 1 only in that 2 g of the iron ion collector prepared in Preparation Example 3 is added in step S102.
[0071] Example 4 and Example 5 are ultra-white high borosilicate glass, which differ from Example 1 only in that the ratio of the raw materials is adjusted, as shown in Table 1:
[0072] Table 1: Formula of high borosilicate glass in Example 1, Example 4 and Example 5
[0073] Example 1 Example 4 Example 5 Pre-treated quartz sand / kg 7.5 7 8 <![CDATA[B2O3 / kg]]> 1.2 1 1.5 <![CDATA[Al2O3 / kg]]> 0.4 0.5 0.3 Sodium chloride / kg 0.15 0.15 0.15 <![CDATA[Na2O / kg]]> 0.5 0.6 0.4
[0074] Example 6, an ultra-white high-borosilicate glass, is different from Example 1 only in that the iron ion collector prepared in Preparation Example 1 is replaced by an equal amount of the iron ion collector prepared in Preparation Example 4.
[0075] Example 7, an ultra-white high-borosilicate glass, is different from Example 1 only in that the iron ion collector prepared in Preparation Example 1 is replaced by an equal amount of the iron ion collector prepared in Preparation Example 5.
[0076] Example 8, an ultra-white high-borosilicate glass, is different from Example 1 only in that the iron ion collector prepared in Preparation Example 1 is replaced by an equal amount of the iron ion collector prepared in Preparation Example 7.
[0077] Example 9, an ultra-white high-borosilicate glass, is different from Example 1 only in that the iron ion collector prepared in Preparation Example 1 is replaced by an equal amount of the iron ion collector prepared in Preparation Example 8.
[0078] Comparative Example
[0079] Comparative Example 1 is an ultra-white high-borosilicate glass, which is different from Example 1 only in that the iron ion collector prepared in Preparation Example 1 is replaced by an equal amount of the iron ion collector prepared in Preparation Example 6.
[0080] Comparative Example 2 is an ultra-white high-borosilicate glass, which is different from Example 1 only in that the iron ion collector prepared in Preparation Example 1 is not added in step S102.
[0081] Comparative Example 3, an ultra-white high borosilicate glass, is different from Example 1 only in that the pretreatment steps of the quartz sand are:
[0082] S101. Add 1 kg of quartz sand (average particle size 2 mm) to deionized water and immerse for 7 days;
[0083] S102. The pH value of the solution was adjusted to 3.5, 3 g of the iron ion collector prepared in Preparation Example 1 and 0.8 g of sodium dodecylbenzene sulfonate were added, and the mixture was stirred for 30 min;
[0084] S103. Pre-treated quartz sand is obtained by centrifugal separation, filtering, washing and drying.
[0085] Comparative Example 4, an ultra-white high borosilicate glass, is different from Example 1 only in that the pretreated quartz sand is replaced by an equal amount of quartz sand that has not been pretreated.
[0086] Performance testing
[0087] 1. Iron ion content test: Inductively coupled plasma emission spectroscopy was used to quantitatively test the iron content in the high borosilicate glass obtained in the embodiment and the comparative example.
[0088] 2. Light transmittance test: According to the relevant records in GB / T 2680-2021 "Determination of visible light transmittance, direct sunlight transmittance, total solar energy transmittance, ultraviolet light transmittance and related window glass parameters of architectural glass", the light transmittance (%) of the high borosilicate glass obtained in the examples and comparative examples was tested.
[0089] The above test results are shown in Table 2:
[0090] Table 2 Performance test results
[0091]
[0092] According to Table 2, in combination with Example 1, Example 8 and Example 9, it can be seen that Example 8 has a lower iron content and better light transmittance than Example 1. The reason is that the iron ion collector in Example 8 is also coordinated with manganese ions, which can help oxidize the divalent iron ions in the leachate into trivalent iron ions, which is more conducive to the adsorption and removal of iron ions; while the excessive number of coordinated manganese ions in Example 9 will affect the ability of tannic acid / polyacrylamide to coordinate iron ions, thereby causing the light transmittance to decrease compared with Example 8.
[0093] Combining Example 1, Comparative Examples 1 to Comparative Examples 4, it can be seen that in Comparative Example 1, since no tannic acid is added to the polyacrylamide for compounding, the ability of the iron ion collector to fix iron ions will be affected, resulting in an increase in iron content and a decrease in transmittance; in Comparative Example 2, no collector is added, and the iron ions in the leachate are difficult to be further separated and filtered from the quartz sand. In Comparative Example 3, most of the iron ions are still fixed inside the quartz sand without acid leaching, and the iron ion collector is difficult to interact with the internal iron ions, resulting in a greatly reduced effect of removing iron ions. In Comparative Example 4, the quartz sand is not pretreated, and the impurity iron content in the raw material is high, which will seriously affect the transmittance of the obtained high borosilicate glass, and the required ultra-white high borosilicate glass cannot be obtained.
[0094] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0095] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An ultra-white high borosilicate glass, characterized in that: Including the following raw materials by mass: 70-80 parts of pre-treated quartz sand; B2O3 10-15 parts; Al2O3 3-5 parts; 1-2 parts of clarification aid; Na2O 4-6 parts; The pretreated quartz sand is obtained by acid leaching and pretreatment with an iron ion collector; the iron ion collector is tannic acid / polyacrylamide hydrogel.
2. The ultra-white high borosilicate glass according to claim 1, characterized in that: The pretreatment of quartz sand includes the following specific process steps: S101. Add quartz sand to a strong acid aqueous solution and immerse for 5 to 10 days; S102. Adjust the pH value of the solution to 3 to 4, add an iron ion collector and a dispersant, and stir and mix for 30 to 40 minutes; S103. Pre-treated quartz sand is obtained by centrifugal separation, filtering, washing and drying.
3. The ultra-white high borosilicate glass according to claim 2, characterized in that: The added amount of the iron ion collector is 0.2-0.4% of the mass of the quartz sand.
4. The ultra-white high borosilicate glass according to claim 2, characterized in that: The dispersant comprises a combination of one or more of sodium dodecylbenzene sulfonate, sodium lignin sulfonate, sodium lauryl ether sulfate and polyvinyl pyrrolidone; and the added amount of the dispersant is 0.05-0.1% of the mass of the quartz sand.
5. The ultra-white high borosilicate glass according to claim 2, characterized in that: The particle size of the quartz sand is 0.5-5 mm.
6. The ultra-white high borosilicate glass according to claim 1, characterized in that: The raw materials of the tannic acid / polyacrylamide hydrogel include acrylamide and tannic acid in a mass ratio of 100:(4-6).
7. The ultra-white high borosilicate glass according to claim 6, characterized in that: The tannic acid / polyacrylamide hydrogel is coordinated with manganese ions.
8. The ultra-white high borosilicate glass according to claim 7, characterized in that: The tannic acid / polyacrylamide hydrogel is prepared according to the following method: Preparation of hydrogel: Add tannic acid to water, stir to dissolve, then add acrylamide, initiator and cross-linking agent, stir and mix until completely dissolved, raise the temperature to 60-70°C, keep warm for 1-2 hours, wash and filter to obtain tannic acid / polyacrylamide hydrogel; Coordinated manganese ions: Disperse tannic acid / polyacrylamide hydrogel in water, adjust the pH value to 6-6.5, increase the temperature to 30-35°C, add water-soluble manganese salt, stir the reaction for 30-60 minutes, and then keep warm at 4-6°C in a nitrogen atmosphere for 6-8 hours. Finally, wash, evaporate and freeze-dry to obtain tannic acid / polyacrylamide hydrogel coordinated with manganese ions.
9. The ultra-white high borosilicate glass according to claim 8, characterized in that: The added amount of the water-soluble manganese salt is 1-3% of the mass of the tannic acid / polyacrylamide hydrogel.
10. A method for preparing ultra-white high borosilicate glass according to any one of claims 1 to 9, characterized in that: The process steps include: S201. Weigh the corresponding mass fractions of raw materials and mix them to obtain a premix; S202. The premix is melted at a high temperature of 1650 to 1750° C. to obtain a borosilicate glass liquid; S203. After being fully stirred and clarified, the borosilicate glass liquid is gradually cooled to remove bubbles and impurities, and finally formed and annealed to obtain ultra-white high-borosilicate glass.